Social Historical Reading Of Communication Theories - بن سولة نورالدين (University of Eloued جامعة الوادي, 2024)
Through this scientific paper, we seek to discuss the importance of endoscopy in the field of communication, which is very important in addressing the complexity of information and communication technology in society, It has become intertwined in many fields of knowledge, both in the human and social sciences and in the applied and natural sciences. On the other hand, we observe a stereotype in communication research in terms of its treatment of the explanatory theories of communication phenomena and a metaphor for theories that grew in the last century under different historical events and social conditions than in our present era. in addition to attempts to build new theories at a rapid and changing technological pace. We see it as a matter of great magnitude that needs to be discussed to open up new horizons in scientific research beyond stereotypes. So we try to bring this vision forward through the historical sociotracking of the most prominent communication theories and highlight the importance of geographical and temporal context in the endoscopy process to understand and interpret communication phenomena, Most important is the technological inequality that can exist between societies or even between micro-groups within a single period.
Keywords: Communication Theories; Socio-Historical; Context; Temporal Context; Theoretical Stereotype; Communication Phenomenon